Are Deposits a Stable Source of Funding for Microfinance Institutions? - Abakaeva, Julia; Glisovic-Mezieres, Jasmina (World Bank, Washington, DC, 2012)
Poor people save. The conventional view is that low-income depositors transact more frequently than holders of larger accounts and are more prone to income disruptions from natural disasters, health issues, crime, and other factors. This perception makes financial institutions stepping into the under-served low-income space worry about whether they can use small deposits to fund their lending operations. But new research finds that under normal circumstances, aggregate balances for low-income accounts move gradually, and they are not prone to abrupt month-by month swings. This should make liquidity management easier because it gives the institutions enough time to adjust to changes in deposit supply over several months.